2021
DOI: 10.1101/2021.10.05.463008
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

How does temperature affect the dynamics of SARS-CoV-2 M proteins? Insights from Molecular Dynamics Simulations

Abstract: Enveloped viruses, in general, have several transmembrane proteins and glycoproteins, which assist the virus in entry and attachment onto the host cells. These proteins also play a significant role in determining the shape and size of the newly formed virus particles. The lipid membrane and the embedded proteins affect each other in non-trivial ways during the course of the viral life cycle. Unravelling the nature of the protein-protein and protein-lipid interactions, under various environmental and physiologi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 63 publications
0
4
0
Order By: Relevance
“…Systems initial minimization was performed to remove bad contacts using the steepest descent algorithm. In this step, systems were heated with a Berendsen thermostat at 310 K in the canonical ensemble (NVT) over 7 ns, an adequate temperature to use in SARS-CoV-2 M protein MD simulations [ 81 ]. Pressure was kept constant at one bar with an isothermal–isobaric ensemble (NPT) for 20 ns with a semi-isotropic pressure coupling algorithm [ 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…Systems initial minimization was performed to remove bad contacts using the steepest descent algorithm. In this step, systems were heated with a Berendsen thermostat at 310 K in the canonical ensemble (NVT) over 7 ns, an adequate temperature to use in SARS-CoV-2 M protein MD simulations [ 81 ]. Pressure was kept constant at one bar with an isothermal–isobaric ensemble (NPT) for 20 ns with a semi-isotropic pressure coupling algorithm [ 82 ].…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, coarsegrained simulations by Rath et al suggest that lower temperatures might be detrimental to M protein dimer interactions, possibly due to an energy barrier from lipid packing around the dimers. 2 In light of these studies and the data from our simulations, we suggest that M protein dimers likely need to interact with each other and possibly with E protein pentamers in order to generate the global curvature needed for budding. As expected given the local curvature in the corrected 4M simulation, the membrane surface areas of the cytosolic and lumenal leaflets stayed roughly equal over the course of the trajectory, though these surface areas fluctuated more than was seen in the 4E simulation (Figure 3B).…”
mentioning
confidence: 60%
“…This is consistent with our previous simulation in which the only protein–protein interactions came from a few random contacts between unstructured loops. Since recent studies have suggested that M dimers actually do interact with each other, , we hypothesize that the lack of interactions in our simulation might be due to the simulation’s temperature of 300 K. This temperature is standard for molecular dynamics studies but is lower than human body temperature. Indeed, coarse-grained simulations by Rath et al suggest that lower temperatures might be detrimental to M protein dimer interactions, possibly due to an energy barrier from lipid packing around the dimers .…”
mentioning
confidence: 98%
See 1 more Smart Citation